Fallacies and Possible Remedies of the SYNTAX Score. (15th December 2020) - He, Yong-Ming; Shen, Li; Ge, Jun-Bo
Abstract : Quite a few studies have revealed the clinical values regarding the outcome predictions in the cohort of the Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) trial and decision-making with the SYNTAX score. The Evaluation of Xience Everolimus-Eluting Stent Versus Coronary Artery Bypass Surgery for Effectiveness of Left-Main Revascularization (EXCEL) and Nordic-Baltic-British left main revascularization (NOBLE) studies are the largest international randomized studies so far, comparing percutaneous coronary intervention (PCI) and coronary artery bypass graft (CABG) in the treatment of left main coronary artery disease. Unfortunately, both studies failed to validate the value of the SYNTAX score in the selection of revascularization strategies for patients with coronary artery diseases (CAD).. This scenario prompted us to reconsider the inherent fallacies of the SYNTAX score in its derivation. We pointed out eight fallacies for the SYNTAX score in this paper. A recently developed Coronary Artery Tree description and Lesion EvaluaTion (CatLet) score, available at http://www.catletscore.com, a novel angiographic scoring system, could be the remedies for the SYNTAX score.